Use of science and philological culture journals from the Philological Sciences reading room collection (Confluenţe Bibliologice, 2012)
This article briefly presents the collection of periodicals of the Philological Sciences reading room and their use by users. As a result of research conducted on the basis of this collection, both the most requested and the least used serial titles were determined. The research allows us to determine the titles required for subscription.
Keywords: periodicals; collection of USARB SL; poll